ANALISIS KOMPARATIF PERSEPSI GURU SEKOLAH MENENGAH ATAS TERHADAP PROFESI AKUNTAN PUBLIK DAN PROFESI LAINNYA - Sri - Marjani (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
ABSTRACT The purpose of this research is to know the perception of high school teacher (SMA) against the profession of public accountant comparable to other professions, medical profession and advocate. This research data are derived from primary data. The population in this research is high school teachers in Surakarta. The sampling technique with the purposive sampling are guidance counseling teachers and class guardian. The statistical methods used to test the research hypothesis is descriptive analysis, T-test and ANOVA. The results of this research show that high school teacher perception of the profession of public accountant is lower than the medical profession but higher than the profession of advocate. There is no difference in the perception of high school teacher’s profession of public accountant and the other professions, medical profession and advocate based on gender. There is no difference in the perception of high school teacher’s profession of public accountant and the other professions based on experience. Keywords: perception, high school teacher, public accountant.